Strengthening the Patent Gatekeeper: The Mandatory Disclosure of Origin in Indonesia’s Intellectual Property Regime - Efridani Lubis; Nurwidiatmo Nurwidiatmo; Heru Widodo; Prastopo Prastopo; Zinatul Ashiqin Zainol (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2026)
The enactment of Law No. 65 of 2024 has fundamentally transformed the legal status of Mandatory Disclosure of Origin (MDO) within Indonesia’s patent regime. While previous studies have primarily examined MDO as a mechanism for preventing biopiracy and facilitating access and benefit-sharing, limited attention has been paid to its evolving role as a substantive patentability requirement and its philosophical foundation within Indonesia’s legal system. This article addresses that gap by examining how Article 26 of the amended Patent Law redefines the disclosure of genetic resources and traditional knowledge from a procedural obligation into a substantive legal mandate. Using a statutory, conceptual, and comparative legal approach, this study analyzes the transformation of Article 26 in light of Law No. 65 of 2024, the Nagoya Protocol, and the 2024 WIPO Treaty on Intellectual Property, Genetic Resources and Associated Traditional Knowledge. The analysis further employs an axiological perspective to evaluate the compatibility of MDO with the constitutional values embodied in Pancasila. The findings demonstrate that the amended Patent Law significantly strengthens the gatekeeping function of the Indonesian patent system by linking patent validity to transparency regarding the origin and lawful acquisition of genetic resources and traditional knowledge. The reform establishes a legal framework that integrates Prior Informed Consent (PIC), Access and Benefit-Sharing (ABS), and post-grant accountability mechanisms, thereby enhancing protection against biopiracy. Furthermore, the study finds that the strengthened MDO regime reflects a shift from a predominantly individualistic intellectual property paradigm toward a distributive justice model grounded in the Second and Fifth Principles of Pancasila. This article argues that the strengthened gatekeeper model represents a form of decolonial intellectual property reform that balances private innovation with collective rights, reinforces national sovereignty over biological resources, and provides a normative foundation for equitable benefit-sharing in the emerging bioeconomy.